Adaptive Extended Kalman–like Observer for Uncertain Photovoltaic Systems. Issue 29 (2019) - Stitou, Mohamed; Fadili, Abderrahim El; Chaoui, Fatima Zahra; Giri, Fouad
Abstract: The problem of state and parameter estimation in photovoltaic (PV) systems is addressed. The maximum power point tracking (MPPT) techniques and controllers design involve the PV generator (PVG) delivered voltage and current. However, in situations where PV arrays are located in a remote site from the control unit of the converter, so as to profit from good solar radiation, PVG voltage and current measurements become difficult. From other side, the use of long PV cable between the PVG and the converter would produce substantial voltage drops in the cable, which would consequently result in MPPT control inaccuracies if only voltage and current sensed in the converter input side of the cable are used instead. To avoid this problem, an adaptive Kalman–like observer for PV systems is designed, in this paper. Using only voltage and current measurements in the converter input, the observer performs online estimation of the PVG output voltage and current as well as of the cable resistance and inductance, regardless of these parameters uncertainties. The convergence of the system state and parameters is shown by simulation.